2017
DOI: 10.1111/jhn.12526
|View full text |Cite
|
Sign up to set email alerts
|

Quality of development and reporting of dietetic intervention studies in primary care: a systematic review of randomised controlled trials

Abstract: Background: High-quality research methodologies and clear reporting of studies are essential to facilitate confidence in research findings. The aim of the present study was to conduct an in-depth examination of the methodological quality and reporting of studies included in a recent systematic review of dietitians' effectiveness at providing individualised nutrition care to adult patients. Methods: The methodological quality and reporting of 27 Randomised Controlled Trials (RCTs) were appraised using the UK Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Moreover, a recent systematic review observed that none of the reviewed dietetic intervention studies in primary care met more than half of the UK Medical Research Council Guidance criteria, and no studies met all criteria of the CONSORT checklist, suggesting the need for improvement in reporting and design of nutritional interventions in general. 131 No other study, however, has graded evidence from meta-analyses on risk factors and nonpharmacological and nonsurgical treatments for obesity as the present work does.…”
Section: Comparison With Other Studiesmentioning
confidence: 87%
“…Moreover, a recent systematic review observed that none of the reviewed dietetic intervention studies in primary care met more than half of the UK Medical Research Council Guidance criteria, and no studies met all criteria of the CONSORT checklist, suggesting the need for improvement in reporting and design of nutritional interventions in general. 131 No other study, however, has graded evidence from meta-analyses on risk factors and nonpharmacological and nonsurgical treatments for obesity as the present work does.…”
Section: Comparison With Other Studiesmentioning
confidence: 87%
“…Despite this there appears to be a need for evidence on the involvement of dietitians in the delivery of rural dietary interventions, given the positioning of the profession in the Australian healthcare system 34 . A recent review that assessed the effectiveness of dietitians involved 26 RCT diet intervention studies noted that the current quality of evidence of effectiveness of dietitians providing individual advice in RCTs is poor 35 . The authors emphasised there is a need for better collaboration between researchers and dietitians in the design and delivering dietary interventions 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The range in observed weight change results for the included studies could be explained by real differences or by study artefacts in this evidence base. Potential methodological design factors include: the majority of studies being of less than 12 months duration, lack of attention given to specifying a primary outcome or powering the study sufficiently for that outcome variable, lack of standardized endpoints and their measurement and/or reporting, variation in the control conditions used (from other health professionals delivering dietary advice, to written information to no intervention) and an overall lack of clear description of methods and results which we have reported previously [38]. Most studies did not separate the results by gender, and it is possible that one gender may respond better to individualized dietetic interventions that are traditionally delivered by women in this female-dominated profession.…”
Section: Discussionmentioning
confidence: 99%